Prediction of growth response to GH treatment : a reference guide - Schönau, Eckhard; Rauch, Frank; Blum, Werner F (TMG Healthcare Communications, 2001)
The guide focuses on growth hormone deficiency in children and on its treatment, including the GeNeSIS research programme. Intended for professional public.
GeNeSIS. Next step for growth.
Keywords: růst a vývoj; mutace; Neuroendocrinology; Hormone Replacement Therapy; pediatrie; neuroendokrinologie; genetika, lékařská genetika; Human Growth Hormone; lékařská genetika; endokrinologie; Mutation; lidský růstový hormon; klinická studie jako téma; Clinical Studies as Topic; hormonální substituční terapie; Developmental Disabilities; Growth and Development; vývojové poruchy u dětí; Dwarfism, Pituitary; hypofyzární nanismus; Genetics, Medical